Love comes softly [videorecording (DVD)] - Ashford, William; Thorne, Ken (Love comes softly film series, 2004)
A woman's dream to forge a new life for herself on the great American plains becomes a test of her pioneering spirit, her inner strength, and her undying faith. It was Marty Claridge's dream to build her new life on the frontier with her husband. But when the courageous pioneer woman is suddenly widowed, she's offered a new opportunity-- to marry a widower in a marriage of convenience. What they did not expect was that the marriage would lead to love.